118k views
19 votes
Hi. I need help with this question (see image). Please show workings.


Hi. I need help with this question (see image). Please show workings. ​-example-1

1 Answer

3 votes

Answer:


(dy)/(dx) = -
(18x)/((3x^2+1)^4)

Explanation:

Differentiate using the chain rule

Given

y = f(g(x)) , then


(dy)/(dx) = f'(g(x) × g'(x)

Given

y =
(1)/((3x^2+1)^3) =
(3x^2+1)^(-3) , then


(dy)/(dx) = - 3
(3x^2+1)^(-4) ×
(d)/(dx) (3x² + 1 )

= - 3
(3x^2+1)^(-4) × 6x

= -
(18x)/((3x^2+1)^(4) )

User CMoi
by
5.4k points